Bio-óleo e biogás da degradação termoquímica de lodo de esgoto doméstico em cilindro rotativo - Pedrosa, Marcelo Mendes (2011)
The objective of this study was to produce biofuels (bio-oil and gas) from the thermal treatment of sewage sludge in rotating cylinder, aiming industrial applications. The biomass was characterized by immediate and instrumental analysis (elemental analysis, scanning electron microscopy - SEM, X-ray diffraction, infrared spectroscopy and ICP-OES). A kinetic study on non-stationary regime was done to calculate the activation energy by Thermal Gravimetric Analysis evaluating thermochemical and thermocatalytic process of sludge, the latter being in the presence of USY zeolite. As expected, the activation energy evaluated by the mathematical model "Model-free kinetics" applying techniques isoconversionais was lowest for the catalytic tests (57.9 to 108.9 kJ/mol in the range of biomass conversion of 40 to 80%). The pyrolytic plant at a laboratory scale reactor consists of a rotating cylinder whose length is 100 cm with capable of processing up to 1 kg biomass/h. In the process of pyrolysis thermochemical were studied following parameters: temperature of reaction (500 to 600 ° C), flow rate of carrier gas (50 to 200 mL/min), frequency of rotation of centrifugation for condensation of bio-oil (20 to 30 Hz) and flow of biomass (4 and 22 g/min). Products obtained during the process (pyrolytic liquid, coal and gas) were characterized by classical and instrumental analytical techniques. The maximum yield of liquid pyrolytic was approximately 10.5% obtained in the conditions of temperature of 500 °C, centrifugation speed of 20 Hz, an inert gas flow of 200 mL/min and feeding of biomass 22 g/min. The highest yield obtained for the gas phase was 23.3% for the temperature of 600 °C, flow rate of 200 mL/min inert, frequency of rotation of the column of vapor condensation 30 Hz and flow of biomass of 22 g/min. The non-oxygenated aliphatic hydrocarbons were found in greater proportion in the bio-oil (55%) followed by aliphatic oxygenated (27%). The bio-oil had the following characteristics: pH 6.81, density between 1.05 and 1.09 g/mL, viscosity between 2.5 and 3.1 cSt and highest heating value between 16.91 and 17.85 MJ/ kg. The main components in the gas phase were: H2, CO, CO2 and CH4. Hydrogen was the main constituent of the gas mixture, with a yield of about 46.2% for a temperature of 600 ° C. Among the hydrocarbons formed, methane was found in higher yield (16.6%) for the temperature 520 oC. The solid phase obtained showed a high ash content (70%) due to the abundant presence of metals in coal, in particular iron, which was also present in bio-oil with a rate of 0.068% in the test performed at a temperature of 500 oC.